نحو معالجة التعصب الديني والاجتماعي كآلية لتحقيق الأمن الثقافي في ظل عصر الرقمنة - زغدار, عبد الحق; كواشي, عتيقة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2024)
لم يعد التطرف يرتبط بمنطقة أو ديانة بعينها، وإنما تحول إلى ظاهرة "مُعولمة"، خاصة مع تصاعد قوى اليمين المتطرف وعودة الشعبوية في أوروبا والعديد من المناطق في العالم ،حيث أسهمت فيها بدرجة كبيرة ثورة الاتصالات والتكنولوجيا الحديثة ،ومما لا شك فيه أن تصاعد الصراع باسم الهوية الدينية، وما يرتبط به من استقطاب حاد وعنف طائفي ومذهبي يمثل تهديداً للأمن والاستقرار الإقليمي والدولي، وعليه هناك ضرورة لتحرك دولي فاعل من أجل احتواء الصراعات التي تتخذ من الهوية الدينية ستاراً لها، عبر وسائل الاتصال الحديثة،حتى لا ينزلق العالم إلى أتون حروب دينية مدمرة تعيده إلى عصور الظلام،بدلتحقيق الامن الثقافي و ترقية الثقافة العالمية . Extremism is no longer linked to a specific region or religion, but has turned into a "globalized" phenomenon, especially with the rise of the forces of the extreme right and the resurgence of populism in Europe and many regions in the world, where the revolution in communications and modern technology has contributed to a large extent, and there is no doubt that the escalation of conflict In the name of religious identity, and the severe polarization and sectarian and sectarian violence associated with it, which represents a threat to regional and international security and stability, and therefore there is a need for effective international action to contain conflicts that use religious identity as a cover through modern means of communication, so that the world does not slide into the furnace of wars. A religious destroyer that brings it back to the dark ages, in exchange for achieving cultural security and promoting world culture.